Risk factors associated to falls of hospitalized patients in medical-surgical clinics. - Ribeiro Aguiar, Jefferson; de Oliveira Barbosa, Amanda; Galindo Neto, Nelson Miguel; Aguiar Ribeiro, Marcos; Áfio Caetano, Joselany; Moreira Barros, Lívia (Acta Paulista de Enfermagem, 2019)
Objective: To identify the risk factors associated to falls of hospitalized patients in medical-surgical clinics. Methods: Analytic and descriptive study with a quantitative approach, carried out from June to September 2017 in a large-scale public hospital in the northern area of Ceará state, Brazil. The sample had 155 patients and data collection was made through a structured tool split in five parts: a) Clinical-Epidemiologic Data; b) Mini-mental state examination; c) Morse Fall Scale application; d) Katz Index application; and e) "Fall Risk" Nursing Diagnosis (ND). For statistical analysis, a 5% sample error was taken into consideration. Results: Out of 155 patients, 41.2% (64) had a clinical diagnosis and 58.8% (91) were traumatological patients. Statistic correlation was identified for fall occurrences between hospitalization days (p=0.07), mini mental examination (p=0.048) and Katz (p=0.017) for clinical patients, while traumatological patients presented fall occurrence positive association on variables age (p=0.028) and Katz (p=0.037). Conclusion: Main identified risk factors were: use of auxiliary devices, fall background, post-surgical status, walking difficulties, decreased strength on body extremities, impaired balance, impaired physical mobility, little-known setting, and insufficient non-slip flooring in bathrooms.